P. VIGANÒ - Territories of Urbanism: The Project as Knowledge Producer - Monclús Fraga, Javier (ZARCH, 2021)
Paola ViganòTerritories of Urbanism: The Project as Knowledge ProducerLausanne: EPFL Press, 2016. 300 pp. Tapa dura. Idioma: inglés. 53 € ISBN-10: 2940222894ISBN-13: 978-2940222896